Lymphocyte Subset Abnormalities in Pediatric-Onset Common Variable Immunodeficiency - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; BARIŞ, SAFA (KARGER, 2020)
Introduction: Common variable immunodeficiency (CVID) is characterized by recurrent infections, autoimmunity, lymphoproliferation, hypogammaglobulinemia, and defective antibody production. In CVID, B-cell abnormalities were described to predict end organ involvement and prognosis. Pediatric-onset CVID is much rarer than adult CVID, and lymphocyte subset abnormalities have not been thoroughly evaluated. Objective: We sought to determine lymphocyte subset abnormalities and their association with end organ involvement in pediatric-onset CVID patients. Methods: The clinical manifestations and laboratory findings including absolute numbers and percentages of B-, T-, and NK cell populations were assessed in pediatric-onset CVID patients and compared to age-matched healthy controls. The patients were divided into 2 groups according to age at assessment (pediatric CVID patients: 10-16 years, n = 9; and adult CVID patients: >16 years, n = 13). The comparisons between lymphocyte subsets and organ involvement were also evaluated. Results: Mean age at symptom onset was 18 (3-204) months. All CVID patients with pediatric onset had decreased levels of total and memory B cells, CD4(+) T cells, CD4(+)CD45RA(+) naive T cells, and recent thymic emigrant (RTE) cells. On the other hand, they had increases in CD8(+)CD45RO(+) memory T cells. Interestingly, adult CVID patients demonstrated high frequencies of activated and double-negative T cells, which were unique only for this group of patients. Specific cellular abnormalities associated with the reduction in B and NK cells and increase in CD8(+) T cells were found in patients with bronchiectasis. Moreover, in pediatric CVID patients, low serum IgA levels and decreased numbers of naive T and RTE cells were determined as risk factors for chronic diarrhea. Conclusions: Specific abnormalities in B- and T-lymphocyte compartments were identified in pediatric-onset CVID patients and appear to be associated with end organ manifestations.
Keywords: Common variable immunodeficiency; Pediatric patients; Lymphocyte subsets; End organ involvement; B-CELL; DEFICIENCY; DIFFERENTIATION; CLASSIFICATION; SUBGROUPS; CHILDREN